Islamic Solidarity Values in The Philosophy of Pancasila - Cahyati, Ade Cici Nur; Ariska, Ariska; Shafa, Aulia Nuranida; Azzahra, Nadia; Ardiyanti, Nadya Tri; Ningsih, Yulia; Rizti, Zahwa Ananda (TATHO: International Journal of Islamic Thought and Sciences, 2025)
The application of ukhuwah values in society faces challenges such as social polarization, inter-group conflicts, identity discrimination, and radicalism, which shows that the ideality of ukhuwah in Pancasila has not been achieved. The purpose of this study is to identify the values of ukhuwah in Pancasila. This research uses a literature study approach with indicators of ukhuwah contained in Pancasila. The research data was obtained through journal reviews, and the analysis was conducted with data verification. The findings of this study confirm that the values of ukhuwah basyariyah, watthoniyah, and islamiyah have strong relevance to Pancasila as a moral framework in building brotherhood and harmony amid the diversity of Indonesian society. The theoretical implications of this study show that the values of ukhuwah in Pancasila can be a universal foundation for building harmonious social relations. The limitation of this study is the difference in interpretation regarding the deep meaning of the values of ukhuwah basyariyah, watthoniyah, and islamiyah, especially in its implementation in the life of the nation and state.